Islamic decorative art during the Ottoman ruling in Tripoli, Libya: A study of its educational dimensions / Amira Mohamed Khalifa Eblao - Amira Mohamed , Khalifa Eblao (2019)
During the Ottoman rule in Libya, several different buildings covered with Islamic plant and seometry motifs, which were a kind of transfer of Islamic civilization with the Ottoman feature, and the Muslim artist was able to display it in a manner that is appropriate to the customs and traditions that are the cornerstone of the life of Libyan society. So we should know the types of these motifs classify and understand educational impact related to religion and Islamic belief. This study aims to demonstrate those educational effect included in the decorative arts during the Ottoman rule in Tripoli, and how to use them to formulate general goals for artistic educational curricula in Libya through what Islamic decorative art aims at, linking the educational side on the one hand, and the practical achievement on the other hand, and shedding light on the history of decorative art in Islamic civilization in general, and in the era of the Ottoman Empire in particular in Libya. Hence, it is possible to benefit from them in highlighting the vital features of Islamic civilization within the human history, and here we can say that the problem of study covers the following question: Does Islamic decorative art during the Ottoman rule of Libya contain educational sides that could be used to formulate general goals and materials for technical education In Libya? The research depends on the descriptive inductive approach to identify the concept of decorative art and its educational sides, whether in Islamic civilization or through decorative arts during the rule of the Ottoman Empire, where it could be understood in detail by extrapolating to pave the way for generating general results for the study and the descriptive analytical approach to describe decorative artwork in the study sample. The Content Analysis Approach is applied to analyze the decorations contained in the scientific material related to the subject of the study that was collected in order to state its content, list in detail, and then discuss it. The researcher analyses the educational content, which its vocabulary is derived from the Islamic approach, the educational objectives in general, the objectives of art education in particular, and the Islamic perception of the universe and life. The study reached a set of results that were considered in conclusion, the most important of which is that the Islamic motifs during the era of the Ottoman rule contain a philosophy and educational sides that could be used to formulate the general objectives of educational art materials. Ottoman motifs have a distinguished feature from the rest of the other decorations accompanying the Islamic eras, and Islamic decorative art is closely related to Al-Qur’an and Al-Sunnah.